2007
DOI: 10.1007/s10681-007-9354-1
|View full text |Cite
|
Sign up to set email alerts
|

Yield, yield components and plant architecture in the F3 generation of common bean (Phaseolus vulgaris L.) derived from a cross between the determinate cultivar ‘Prelude’ and an indeterminate landrace

Abstract: Yield, yield components and plant architecture in the F3 generation of common bean (Phaseolus vulgaris L.) derived from a cross between the determinate cultivar 'Prelude' and an indeterminate landrace Abstract Growth trials were conducted outdoors in the UK to determine the yield, yield components and plant architectural differences between determinate and indeterminate Phaseolus vulgaris bean plants. F3 lines derived from crosses between 'Prelude', a determinate cultivar and 'V8', an indeterminate landrace, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
1
19
0
4
Order By: Relevance
“…Plants with a more compact architecture are used in crossovers to select for erectness and precocity, since they exhibit lower production potential compared to prostrate plants. In turn, cultivars with an undetermined growth habit display higher yields than those with a defined habit because vegetative development progresses through the production of new buds, which generate flowers and improve the yield potential (Dawo Sanders & Pilbeam, 2007). However, the ideal plants for mechanical harvesting are those with type I and II growth habits (Miklas & Singh, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Plants with a more compact architecture are used in crossovers to select for erectness and precocity, since they exhibit lower production potential compared to prostrate plants. In turn, cultivars with an undetermined growth habit display higher yields than those with a defined habit because vegetative development progresses through the production of new buds, which generate flowers and improve the yield potential (Dawo Sanders & Pilbeam, 2007). However, the ideal plants for mechanical harvesting are those with type I and II growth habits (Miklas & Singh, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Assim como, em Arabidopsis também foram encontrados receptores distintos para o caráter normal e para o tipo anão (UEGUCHI-TANAKA et al, 2007). E, em feijão o estudo da herança do caráter determinado e indeterminado não conferiu melhoria na altura de inserção de vagens (DAWO et al, 2007).…”
Section: Resultsunclassified
“…Aumentar índice de colheita mecanizada é o principal desafio para a expansão da cultura do feijão e consequente inclusão desta cultura em escala comercial, com possibilidade de mecanização total das operações agrícolas (COSTA; PASQUALETTO, 1999). Outro fator, independente do hábito de crescimento (determinado ou indeterminado) (DAWO et al, 2007), é que os genótipos apresentam a característica comum, ter a estatura dos entrenós basais muito baixa, e não dispor de variabilidade genética como fonte para modificar esta característica por meio do melhoramento de plantas (PESSARAKLI, 2002). Pelo fato dos entrenós basais serem curtos associados à baixa inserção de vagens, ocorrem perdas qualitativa e quantitativa de grãos, como também limita a colheita com automotrizes (TEIXEIRA et al, 1999).…”
Section: Introductionunclassified
“…This is a relevant aspect within the present program because in a breeding program conducted in the State of Paraná, Ceolin et al (2007) found that the trait number of pods per plant, number of seeds per pod, and weight of 100 seeds are important components in order to obtain high productivity. Dawo et al (2007) have determined that the weight of 100 seeds had a response that was not correlated with other production components, where plants that showed a high productivity also had a smaller seed size.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a key aspect to maximize productivity in bean crops has been to select those genotypes that respond well to specific environmental conditions, considering their productivity and survival per unit of area. However, even though there is varied research related to the study of the genetic control of the productivity components of the common bean (Kelly et al, 1998;Ceolin et al, 2007;Dawo et al, 2007) studies about the genetic control of survival in this crop have been relatively undocumented in Brazil. As with any other agricultural crop, mortality in a common bean crop can have direct implications on the productivity and success of the crop.…”
Section: Introductionmentioning
confidence: 99%